1996
DOI: 10.1021/jo951408v
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked LDH Crystals for Lactate Synthesis Coupled to Electroenzymatic Regeneration of NADH

Abstract: Lactate dehydrogenase (LDH) was crystallized from concentrated ammonium sulfate solution and cross-linked with glutaraldehyde to afford long-lived enzymatically active cross-linked crystals (LDH-CLC). The crystals were employed in an electrolytic cell for lactate production from pyruvate, in which the cathode consisted of a carbon electrode containing a coating of lipoamide dehydrogenase (LiDH) immobilized with methyl viologen under a Nafion membrane. This cell was more effective than a similar cell containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…Electrochemical systems using chemically modified [13][14][15][16][17][18] and enzyme-mediated electrodes [19][20][21][22][23][24] have been proposed, and the yield in the active 1,4-NADH produced ranged from ca. 75% on a cholesterolmodified gold-amalgam electrode [13] to ca.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical systems using chemically modified [13][14][15][16][17][18] and enzyme-mediated electrodes [19][20][21][22][23][24] have been proposed, and the yield in the active 1,4-NADH produced ranged from ca. 75% on a cholesterolmodified gold-amalgam electrode [13] to ca.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these two papers [9,10] the authors did not report the yield of the active NADH. Fry et al [11][12][13] have published a series of papers on the reduction of NAD + to NADH on glassy carbon and vitreous carbon electrodes modified by a layer of immobilized methyl viologen and lipoamide dehydrogenase. They showed that the enzyme-catalyzed reduction of NAD + on such modified electrodes results in the production of enzymatically active NADH, but the amount of active NADH produced was not explicitly reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not report the yield of active NADH. Fry et al [7][8][9] have published a series of papers on the reduction of NAD þ to NADH on glassy carbon and vitreous carbon electrodes modified by a layer of immobilized methyl viologen and lipoamide dehydrogenase. They showed that the enzyme catalyzed reduction of NAD þ on such modified electrodes results in the production of enzymatically active NADH, but the amount of active NADH produced was not explicitly reported.…”
Section: Introductionmentioning
confidence: 99%